A Model Calculation of Temperature and Size Dependent Thermoluminescence Intensity from Silicon Nanostructures - Nebiyu Gemechu Debelo (Indonesian Journal of Physics, 2011)
Thermoluminescence (TL) from silicon nanostructures has received considerable attention in recent years. Despite of some theoretical and experimental investigation, the origin and mechanism of TL is not clearly understood. Most of the bulk materials start showing fascinating behaviors as their size is reduced to nano level. The ability to emit light as a consequence of absorption of energy (luminescence) is one of these exotic behaviors. TL is the thermally stimulated emission of light due to absorption of energy from radiation. So, there is a direct relationship between temperature (due to absorption of heat or radiation) and the TL intensity. Starting from the concept of bulk material, we derive the mathematical expression for the temperature and size dependent TL intensity using model calculation. We specifically calculate the TL intensity as a function of temperature and nanoparticle size.